INSTITUTIONALIZATION OF THE PARTY SYSTEM IN KAZAKHSTAN AND RUSSIA: COMPARATIVE ANALYSIS Part I - KARMAZINA, Lydia (CENTRAL ASIA AND THE CAUCASUS, 2008)
The democratic changes underway in the Republic of Kazakhstan and the Russian Federation are focused on the development of parties and the party system, which explains the immense interest in the process demonstrated by their own and foreign communities of political scientists. They concentrate on the emergence and stages of the parties’ development, their legal institutionalization, the “party of power” phenomenon, conduct of parties in election campaigns, the way a definite type of party system took shape, etc. Kazakhstani political scientist D. Satpaev has offered a highly imaginative formula: “some trends of their political development make Russia and Kazakhstan look like identical twins.”1 This is particularly true of the process that resulted in a multi-party system, the similarity of which in both countries has been confirmed by Russian authors as well.2 This article can be described as an attempt to present a comparative analysis of the emergence and development of parties as political institutions in both countries in the context of their histories. This approach suggests parallels, formulates common criteria, identifies common trends, and reveals the specifics of institutionalization of the party arena in Russia and Kazakhstan. Between the 18th and the late 19th centuries Russia and Kazakhstan formed a single state marked by “catching up modernization,” which explains the synthesis (intertwining) and simultaneous existence of pre-capitalist, early capitalist, and developed capitalist relations. This explains the highly unstable social structure and social exclusion of some of the population groups.